Risk of Atrial Fibrillation Following Left Bundle Branch Area Pacing versus Right Ventricular Pacing and Biventricular Pacing: A Systematic Review and Meta-Analysis - Bing Liu; Wenlong Dai; Yake Lou; Yulin Li; Yongquan Wu; Jie Du (Reviews in Cardiovascular Medicine, 2023)
Background: Left bundle branch pacing (LBBP) is a relatively novel physiological pacing strategy with better electrocardiogram characteristics and pacing parameters than other pacing strategies. At present, no meta-analysis or systematic review has examined the risk of atrial fibrillation (AF) after LBBP compared to other pacing strategies. Methods: We searched the PubMed, Embase, and Cochrane Library databases from inception through September 18, 2022 to identify relevant studies reporting AF incidence rates after LBBP. The incidence of AF following LBBP and that associated with other pacing strategies were extracted and summarized for the meta-analysis. We used odds ratios (ORs) and 95% confidence intervals (CIs) as summary estimates. Results: Five studies with 1144 participants were included. The pooled rate of AF was 3.7% (95% CI, 0.8%–8.0%) in the LBBP group and 15.5% (95% CI: 9.6%–22.4%) in the other pacing strategies (right ventricular pacing [RVP] and biventricular pacing [BVP]). Compared with other pacing strategies, LBBP was associated with a lower AF risk (OR, 0.33; 95% CI: 0.22–0.51, I2 = 0.0%; p = 0.485). Similar results were observed for LBBP when compared with RVP (OR: 0.33, 95% CI: 0.22–0.51, I2 = 0.0%, p = 0.641) and BVP (OR: 0.47, 95% CI: 0.01–15.22, I2 = 60.4%, p = 0.112). Conclusions: Compared with BVP and RVP, LBBP was associated with a significantly lower risk of AF. However, further large-sample randomized controlled trials are needed to confirm that LBBP is superior to other pacing strategies in reducing AF risk.